THE ROLE OF EMPLOYEE ENGAGEMENT ON THE INFLUENCE OF WOMEN'S LEADERSHIP AND DISCIPLINE ON EMPLOYEE PERFORMANCE - Sutianingsih Sutianingsih; Ahmad Luthfil Kirom (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to determine, examine and analyze the influence of women's leadership and discipline on the performance of employees of the Sragen Savings and Loan Service Cooperative with employee engagement as an Intervening Variable. The analysis technique used is to use instrument tests which include validity and reliability tests, linearity tests, regression analysis, path analysis, t-tests, F-tests, determination coefficient tests and correlation analysis. The results showed that: Women's leadership has a positive and significant effect on employee engagement. Discipline has a positive and insignificant effect on employee engagement. Women's leadership, discipline, and employee engagement have a positive and significant effect on performance. Women's leadership through employee engagement has a positive and significant effect on performance. However, discipline through employee engagement has a positive insignificant effect on performance. Keywords: Women's Leadership, Discipline, Employee Engagement, Performance